Joining the Club? : Procyclicality of Private Capital Inflows in Low Income Developing Countries - Araujo, Juliana (IMF Working Papers; Working Paper ;, 2015)
Using a newly developed dataset this paper examines the cyclicality of private capital inflows to low-income developing countries (LIDCs) over the period 1990-2012. The empirical analysis shows that capital inflows to LIDCs are procyclical, yet considerably less procyclical than flows to more advanced economies. The analysis also suggests that flows to LIDCs are more persistent than flows to emerging markets (EMs). There is also evidence that changes in risk aversion are a significant correlate of private capital inflows with the expected sign, but LIDCs seem to be less sensitive to changes in global risk aversion than EMs. A host of robustness checks to alternative estimation methods, samples, and control variables confirm the baseline results. In terms of policy implications, these findings suggest that private capital inflows are likely to become more procyclical as LIDCs move along the development path, which could in turn raise several associated policy challenges, not the least concerning the reform of traditional monetary policy frameworks.